Citral-to-Menthol Transformations in a Continuous Reactor over Ni/Mesoporous Aluminosilicate Extrudates Containing a Sepiolite Clay Binder - Simakova Irina L.; Vajglová Zuzana; Mäki-Arvela Päivi; Eränen Kari; Hupa Leena; Peurla Markus; Mäkilä Ermei M.; Wärnå Johan; Murzin Dmitry Yu. (AMER CHEMICAL SOC, 2022)
One-pot continuous synthesis of menthols from citral was performed over 5 wt % Ni supported on a mesoporous aluminosilicate catalyst with sepiolite as a binder at 70 degrees C with a selectivity of 75% to menthols. Catalyst deactivation with time-onstream resulted in a decrease of the conversion and selectivity to menthols at the expense of higher selectivity to isopulegols. Stereoselectivity to isopulegols and menthols only slightly changed with conversion and TOS. A kinetic model capable of describing experimental data for transformations of citral to menthol in a continuous mode was developed. It was based on a detailed reaction network and also comprised deactivation on both metal and acid sites. Numerical data fitting confirmed a good correspondence between the experimental data and calculations.